Intention to leave and associated factors among psychiatric nurses in China: A nationwide cross-sectional study. (June 2019) - Jiang, Feng; Zhou, Huixuan; Rakofsky, Jeffrey; Hu, Linlin; Liu, Tingfang; Wu, Shichao; Liu, Huanzhong; Liu, Yuanli; Tang, Yilang
Abstract: Background: The retention of psychiatric nurses is an important concern for healthcare administrators in China. However, Chinese psychiatric nurses' intention to leave their jobs and the factors associated with it have been scarcely studied. Objective: To investigate Chinese psychiatric nurses' intention to leave their jobs, and to explore the associations between the intention to leave and individual characteristics, job-related factors and job satisfaction. Design: A cross-sectional, anonymous survey of a nationwide sample was conducted. Settings: Thirty-two tertiary psychiatric hospitals in 29 provincial capital cities in China. Participants: All 9907 nurses in 32 hospitals were targeted for this survey conducted in December 2017; 8493 responded (response rate = 85.7%), and 7933 (without logic errors in the data) were included in the analysis. Methods: A questionnaire was used to investigate the respondent's intention to leave their job and to collect data on related factors, including individual characteristics (gender, age, marital status, educational background and self-rated health), job-related factors (professional title, working years, income, work hours, history of patient-initiated violence, perceived respect from patients, social recognition as well as physician-nurse coordination and trust) and job satisfaction. The short version of the Minnesota Satisfaction Questionnaire was used to assess job satisfaction. Chi-square tests and multilevel logistic regression analysis were used to examine associations between an intention to leave and other factors. Results: Among 7933 respondents, 20.2% reported an intention to leave their current jobs. The multiple regression analysis showed that better self-rated health (i.e. OR = 0.373, 95%CI = 0.308-0.452 for good health, reference: poor health), working more than 20 years (OR = 0.479, 95%CI = 0.389-0.590, reference: 20 years or less), higher monthly income (i.e. OR = 0.521, 95%CI = 0.399-0.680 for 6001–8000 RMBs, reference: 4500 RMB or less), perceived patient respect (OR = 0.727, 95%CI = 0.623-0.849), physician-nurse coordination (OR = 0.549, 95%CI = 0.480-0.629) and being satisfied with one's job (OR = 0.373, 95%CI = 0.308-0.452) were negatively associated with an intention to leave; while those who were male (OR = 1.879, 95%CI = 1.605–2.199), working more than 40 hours per week (OR = 1.584, 95%CI = 1.374–1.825) and experienced patient-initiated violence in the past 12 months (OR = 1.566, 95%CI = 1.376–1.781) had a higher odds of reporting an intention to leave. Conclusions: Self-rated health, monthly income, work hours, patient-initiated violence, perceived patient respect, physician-nurse coordination and job satisfaction are significant factors associated with a nurse's intention to quit their job. In order to retain nurses in Chinese tertiary psychiatric hospitals, the government and hospital administrators should consider ways to address these factors.